2022
DOI: 10.3389/fimmu.2022.924667
|View full text |Cite
|
Sign up to set email alerts
|

3’UTR of SARS-CoV-2 spike gene hijack host miR-296 or miR-520h to disturb cell proliferation and cytokine signaling

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has becoming globally public health threat. Recently studies were focus on SARS-CoV-2 RNA to design vaccine and drugs. It was demonstrated that virus RNA could play as sponge to host noncoding RNAs to regulate cellular processes. Bioinformatic research predicted a series of motif on SARS-CoV-2 genome where are targets of human miRNAs. In this study, we used dual-luciferase reporter assays to validate the interaction between 3’UTR of SARS-CoV-2 S (S-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The mechanism could be an interesting topic to further study as many infected people complained about changes in libido as a symptom of long COVID 9 . It was reported that SARS-CoV-2 could hijack the host mRNA and translation system by adjusting host immunity 56 , 57 . Hypothetically, prolactin first increased to regulate cellular immunity and humoral immunity 27 , 28 , and went down along with the recovery condition but took a long time.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism could be an interesting topic to further study as many infected people complained about changes in libido as a symptom of long COVID 9 . It was reported that SARS-CoV-2 could hijack the host mRNA and translation system by adjusting host immunity 56 , 57 . Hypothetically, prolactin first increased to regulate cellular immunity and humoral immunity 27 , 28 , and went down along with the recovery condition but took a long time.…”
Section: Discussionmentioning
confidence: 99%